Retrieval of the planetary boundary layer height in São Paulo from ceilometer and lidar measurements - Santos, Amanda Vieira dos (2023)
Remote sensing systems are powerful tools for atmospheric measurements. In this work, a comparison is presented between two remote sensing systems, a lidar and a ceilometer, in determining the height of the Planetary Boundary Layer (PBL) in the city of São Paulo with the Wavelet Covariance Transform (WCT) method. All data included in this work was collected between February and December, 2021. The systems used were an elastic lidar (MSP-LIDAR I), which operates at 355 nm, 532 nm and 1064 nm, and a ceilometer (Lufft CHM 15k ceilometer) which operates only in the infrared, at 1064 nm. The results are compared in different situations through case studies, which show good agreement between the values obtained with the data from both instruments in calm situations. The monthly average PBL top heights between February and December 2021 and the diurnal average of the PBL are obtained, and it is possible to observe the diurnal and seasonal cycles of the PBL. The results show good applicability of the ceilometer for carrying out measurements to obtain the PBL top height. An application of the data is presented, comparing the heights obtained throughout 2021 with CO2 concentrations measured in three locations in São Paulo, and the results show an anti-correlation between the height of the PBL and the concentration of this gas.